LIMS: Database for livestock performance data. Version 1.2. Computer program with system documentation - Metz, T.; Asfaw, M.D. (International Livestock Research Institute, 1999)
The LIMS (Livestock Information Management System) software package is designed to facilitate the recording and processing of livestock data in developing countries. The package is not specialised for use with any particular species or production system, but can be used with data for any mammal species for a variety of purposes, such as research, extension and commercial production. The objective is to provide user with a computerised tool that allows them to manage complex livestock performance data set, and to provide help in livestock management without relying on specialist computer and data management support. The LIMS software package has been designed to address six key issues in management of livestock performance data, viz, balance of flexibility and standardisation of data definition, documentation and definition of data sets, assistance in deriving non-observed data (breed, parity, mating - parturition connection), data validation and error correction, reporting for animal management, and data extraction and calculation of standard performance traits for statistical analysis. In order to address these various aspects of livestock data management, the LIMS software has a modular design, with different modules addressing each of the above mentioned issues. A generic data set is distributed along with the LIMS software. LIMS is developed in the CLIPPER language. All data in a LIMS data set are stored in dBASE III + compatible data files.